Development of an Anemia Prevention and Solution Program in Pediatric 6–12 Months of Age in Prankratai Hospital Prankratai District, Kamphaeng Phet Province - Vadcharaganon, Podjanee (Journal of Preventive Medicine Association of Thailand, 2022)
Children are the important human resources of the nation. However, the child developmental situation and intelligence level of Thai children tend to decrease due to iron deficiency. This a quasi–experimental research aims to study prevalence rate, related factors, development and trial of iron deficiency anemia prevention and treatment program as well as problems and obstacles in preventing and solving anemia problems in children aged 6–12 months who receive at the well’s baby clinic, Prankratai Hospital, during February–November 2020. Study the data from the medical record and interview form. Data were analyzed by descriptive statistics (frequency, percentage, mean, standard deviation), Chi–square test, Odds ratio, Paired–samples T test with a significance level of 0.05 and content analysis. The results found that: The sample of 248 people, males (54.8%), average age 8.72 months, the anemia prevalence rate (Hb<11g/dL) was 35.9%. The majority of primary caregivers are fathers or mothers, aged 30–50, higher secondary education/vocational, agriculture, family income 10,001–30,000 baht/month. Factors that were statistically related and risk factor for anemia in children were age 6–8 months (OR = 2.398; p = 0.001), birth weight less than 2500 grams (OR = 4.058; p<0.001), breastfed and formula feeding (OR = 26.527; p<0.001), weight unmatched (OR = 1.854; p = 0.021), disproportionate nutrition (OR = 2.733; p<0.001), with underlying/common disease (OR = 4.335; p<0.001), MCV <80 fl (OR = 1.434; p = 0.024), neutropenia and small size (OR = 2.041; p = 0.016), primary caregiver graduated from primary school (OR = 3.082; p = 0.001) and the family earns less than 10,000 baht/month (OR = 3.082; p<0.001). After participating in the program, the children had Hb>11g/dL(94.4%), it was also found that the automatic blood count (CBC) after joining the program were higher than before (p<0.05). The main problems and obstacles in the implementation were 1) not taking medicines as recommended by the doctor 2) not eating all 3 meals and groups 3) participating in the program not due to have to move with the family due to poverty. Based on the findings, anemia is a common problem in children, Therefore, it is necessary to implement an effective prevention and treatment program for iron deficiency anemia, and follow–up these children to know the factors associated with the occurrence of anemia in the end.